2010
DOI: 10.1007/s12603-010-0269-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicians and caregivers: Ready and waiting for increased participation in clinical research

Abstract: Progressive development of pharmacotherapy for Alzheimer's disease (AD) as well as non-pharmacological treatments is critically dependent on the timely recruitment of appropriate subjects for clinical trials. Accordingly, the IMPACT survey sought to determine the level of awareness of clinical trials and the willingness to foster patient involvement/participation in research studies. IMPACT survey participants were recruited via the Internet in equal numbers from 5 European countries-France, Germany, Italy, Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…A recent European study found that physicians had a low awareness of clinical research opportunities for their patients but expressed a high willingness to refer patients to such studies. 11 One small US study found that physicians were reluctant to refer patients because of concerns about perceived harm (such as risk of invasive procedures and stigma of diagnosis in the absence of effective treatment) and fear of losing patients to other providers caring for patients in the clinical research setting. 12 …”
Section: Challenges To Alzheimer’s Trial Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent European study found that physicians had a low awareness of clinical research opportunities for their patients but expressed a high willingness to refer patients to such studies. 11 One small US study found that physicians were reluctant to refer patients because of concerns about perceived harm (such as risk of invasive procedures and stigma of diagnosis in the absence of effective treatment) and fear of losing patients to other providers caring for patients in the clinical research setting. 12 …”
Section: Challenges To Alzheimer’s Trial Recruitmentmentioning
confidence: 99%
“…To better serve participants and their study partners directly, study sites can be conveniently located, or, more effectively, study visits can take place in a participant’s home. 11,30 Such alterations in study design, such as in-home visits or altering the likelihood of receiving a drug versus placebo, may prove cost-effective by improving the recruitment and retention of participants with nonspousal study partners and help build trust to gain participation from underrepresented groups.…”
Section: Strategy Recommendationsmentioning
confidence: 99%
“…For a more complete description of survey methodology, see the article by Jones et al in this issue (6).…”
Section: Practicementioning
confidence: 99%
“…Although several studies 4,13,1517 have been performed to identify variables that influence physician enrollment of patients in clinical trials and recommendation of trial participation to their patients, this type of research has not yet been thoroughly performed in veterinary medicine. The objectives of the study reported here were to survey small animal practitioners to ascertain their attitudes toward enrollment of their patients in veterinary clinical trials, particularly the influence of experimental and other trial variables on their likelihood of recommending clinical trial participation to clients for their pets.…”
mentioning
confidence: 99%